Towards Universalization of Primary Education in Asia and the Pacific: Country Studies China. - United Nations Educational, Scientific, and Cultural Organization, Bangkok (Thailand). Regional Office for Education in Asia and the Pacific; United Nations Educational, Scientific, and Cultural Organization, Bangkok (Thailand). Regional Office for Education in Asia and the Pacific ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
This publication discusses the provision of primary education to children in the People's Republic of China (PRC). Chapter 1 offers a general survey, focusing on the historical background of education since the 1949 revolution, the new school system, educational administration, primary education, and educational finance. Chapter 2 reports state policy for making elementary education universal. Particular attention is given to special purpose schools, controlled population growth, and educational policy concerning regulations for full-time schools, reform of the school system, textbook production, and training primary school teachers. Chapter 3 briefly describes the PRC's project and plan of universal primary education. Chapter 4 presents census data on enrollment, discusses educational problems, and reports proposals for raising the quality of primary education. (RH)
Availability: UNIPUB, 10033/F, Martin Luther King Jr. Highway, Lanham, MD 20706-4391 (Complete volume $52.50 in U. S. funds).
ERIC Note: In: "Towards Universalization of Primary Education in Asia and the Pacific: Country Studies"; see PS 016 069.
Microfiche.
Ashik
Keywords: Educational Change; Educational History; Educational Objectives; Educational Policy; Elementary Education; Equal Education; Foreign Countries; Population Growth; Special Schools; China